Photobiomodulation With a Continuous Wave Red Laser (660 nm) as Monotherapy for Adult Alopecia Areata: A Case Presentation: PBMT for alopecia areata - Palma, Luiz Felipe; Campos, Luana; Arvate Ãlvares, Cristina Maria; Verardi Serrano, Rafael; Carvalho de Moraes, LuÃs Otávio (Journal of Lasers in Medical Sciences, 2023)
Introduction: Alopecia areata (AA) is an autoimmune, inflammatory, non-scarring hair loss in which T-cells target hair follicles. Given that the available therapeutic options generally do not induce and sustain remission of AA effectively and many adverse effects may occur, monochromatic light sources have been recently gaining attention from clinicians. Therefore, the present paper aimed to report the first case in which photobiomodulation therapy (PBMT) with a continuous wave red laser (660 nm) was used as monotherapy for AA. Case Presentation: An isolated round area of complete hair loss was subjected to daily PBMT sessions, resulting in significant regrowth (hair of normal coloration and thickness) within 7 days. On the 21st day, the patient’s aesthetic concern was completely resolved. Conclusion: PBMT with a continuous wave red laser seems to be a promising therapeutic option for the treatment of AA; however, additional studies are necessary to obtain more robust evidence.